Sodium aescinate inhibits microglia activation through NF-κB pathway and exerts neuroprotective effect - Xu, Fei; Jiang, Yiguo; Wang, Xiaoyu; Shen, Li; Yan, Yan; Guo, Dongkai; Wang, Cheng (Frontiers in Pharmacology, 2023)
Background: Microglia are resident immune cells of the central nervous system that sense environmental changes and maintain central nervous system homeostasis. Dysfunctional microglia produce toxic mediators that lead to neuronal death. Recent studies suggest that Sodium Aescinate has a neuroprotective effect. However, it is unclear whether Sodium Aescinate exerts neuroprotective effects by inhibiting activation of microglia. Method: Traumatic brain injury and lipopolysaccharide neuroinflammation model were used to evaluate the microglia activation in vivo. BV2 and primary microglia cells were used to assess the microglia activation in vitro. Molecular docking technique was used to predict the binding energy of Sodium Aescinate to NF-κB signaling pathway proteins. Result: Sodium Aescinate inhibited microglial activation in-vivo and in-vitro. Sodium Aescinate inhibited the activation of microglia in Traumatic brain injury and lipopolysaccharide mouse models. Sodium Aescinate also inhibited the expression of inflammatory proteins in BV2 and primary microglia cells. Western blot experiment showed that SA inhibited the activation of NF-κB pathway in BV2 and primary microglia cells. Molecular docking results also showed that Sodium Aescinate had a better affinity with the core protein of the NF-κB pathway. Western blot identified that SA inhibited activation of NF-κB pathway. In Traumatic brain injury model and conditioned medium experiment, Sodium Aescinate pretreatment inhibited inflammation and protected neuron. Conclusion: Our study confirmed that the protection effects of Sodium Aescinate on neurons by inhibiting microglia activation through NF-κB pathway.